Mechanical Performance of Recycled Plastic-Based Paving Blocks with Sand and Fly Ash Fillers - Mochammad Qomaruddin; Adi Noor Fakhriyan; Yayan Adi Saputro; Yulita Arni Priastiwi; Fatchur Roehman; Nasyiin Faqih; Arif Hidayat; Akhmad Firdos Khoiril Khitam (Advance Sustainable Science Engineering and Technology, 2026)
The use of recycled plastic waste as a binder for paving blocks has been reported in a number of previous studies. However, most of these studies focus on feasibility and do not clearly explain how different plastic types behave mechanically over time. In this study, the compressive strength performance of paving blocks made from polypropylene (PP), polyethylene terephthalate (PET), and high-density polyethylene (HDPE) was experimentally compared using sand or fly ash as fillers. All mixtures were prepared with a fixed composition of 60% plastic and 40% aggregate. Compressive strength testing was carried out at 28 and 56 days using three specimens for each mix. The results show that the HDPE–sand mixture achieved the highest compressive strength at 28 days, reaching 15.7 MPa. Nevertheless, a noticeable reduction in strength was observed at 56 days, particularly in the HDPE-based mixtures. This reduction is mainly associated with polymer shrinkage and the development of interfacial stresses between the plastic binder and the aggregates. Overall, the results indicate that plastic-based paving blocks can meet the requirements of SNI 03–0691–1996 for light-duty applications, although their long-term mechanical stability remains a limitation that needs further attention.